Nutritional care in hospital patient safety: evidence for a new health policy objective - Navarro Vera, Lola (Revista Universidad de Guayaquil, 2015)
Health care should focus on reducing the suffering of patients and not contribute to increase it. Damage resulting from failures in the hospital nutritional care, produces a substantial burden in terms of morbidity and mortality in patients around the world, however, in Ecuador still passes unnoticed by many specialists and those responsible for health administration. Assessment of nutritional status should be mandatory and widely adopted in all hospital services, which along with adequate management protocols, will reduce the incidence of hospital malnutrition and improve the evolutive prognosis. To include nutritional care in practices and health policies is essential to improve the conditions of patient safety and quality of hospital care.